Introduction to virus origins and their role in biological evolution - Domingo, Esteban (Virus as Populations, 2020)
Viruses are diverse parasites of cells and extremely abundant. They might have arisen during an early phase of the evolution of life on Earth dominated by ribonucleic acid or RNA-like macromolecules, or when a cellular world was already well established. The theories of the origin of life on Earth shed light on the possible origin of primitive viruses or virus-like genetic elements in our biosphere. Some features of present-day viruses, notably error-prone replication, might be a consequence of the selective forces that mediated their ancestral origin. Two views on the role of viruses in our biosphere predominate; viruses considered as opportunistic, selfish elements, and viruses considered as active participants in the construction of the cellular world via the lateral transfer of genes. These two models have a bearing on viruses being considered predominantly as disease agents or predominantly as cooperators in the shaping of differentiated cellular organisms.